06.01 Intra-articular injection of cadmium protects arthritic joints from inflammation and destruction. (1st March 2017) - Bonaventura, Paola; Courbon, Guillaume; Lamboux, Aline; Lavocat, Fabien; Marotte, Hubert; Albarede, Francis; Miossec, Pierre
Abstract : Background: There has been no recent progress in the intra-articular treatment of joint inflammation. Rheumatoid arthritis (RA) synovium hyperplasia is sustained by the secretion of pro-inflammatory cytokines (IL-17/TNF-α), synergistically contributing to chronicity. Since inflammation up-regulates trans-membrane Zinc (Zn) importers, the effects of its binding-competitor Cadmium (Cd) were tested on synoviocytes, synovium explants and in a rat arthritis model in order to reduce hyperplasia and inflammation. Materials and methods: After exposure to IL-17/TNF-α and Cd, Cd-kinetics and Cd-cell content were measured by ICP-MS, while Zn/Cd-transporter gene expression (Zrt-Irt-like protein-8, ZIP-8, importer and metallothioneins-1, MT-1, metal homeostasis regulators) by q-RT-PCR. Synoviocyte viability and apoptosis were measured by neutral red and annexin-V staining. IL-6 levels in synoviocyte and biopsy supernatants were measured by ELISA. Adjuvant induced arthritis rat model was used for in vivo Cd-injection into hind ankle joints. Clinical scores were evaluated. Immune cell recruitment was quantified after H and E staining. Micro-tomography and safarin-O staining were used to measure bone/cartilage loss. The potential Cd-spread was measured in different body reservoirs. Results: After synoviocyte exposure to IL-17/TNF-α combination, ZIP-8 and MT-1s gene expressions increased up to 5.3±3.1 fold and 5.0±0.9 fold respectively, compared to the untreated condition (p<0.05). Combined Cd-cytokine exposure further enhanced MT-1s expression up to 93.3±32.1 fold. Through the transporter enhanced expression, Cd content in inflammatory synoviocytes increased two-fold. RA synoviocytes were sensitised toward apoptosis by exposure to the Cd/cytokine combination with an 80% reduction of cell viability in comparison to control (p<0.01), after 5 days of culture. Moreover, Cd-cytokines association reduced IL-6 production in vitro (up to 83%, after 5 days, p<0.05) and ex-vivo (up to 94%, after 8 days, p<0.01). Intra-articular Cd injection improved arthritis, reducing clinical scores (arthritic score reduced from 4 to 2, p<0.01), inflammatory cell recruitment (up to 50%, p<0.01) and bone/cartilage destruction. The use of 1 ppm of Cd provided the best risk/benefit ratio, without toxic effects on other cell types and organs. Conclusion: The anti-proliferative and anti-inflammatory properties of low-dose Cd may represent a new therapeutic approach for the local treatment of synovitis and hyperplasia in arthritis and other joint diseases.